37. KNOWLEDGE, ATTITUDE OF HEALTH STAFF ABOUT ADVERSE DRUG REACTIONS REPORTING IN VINMEC TIMES CITY HOSPITAL IN 2023 (Vietnam Journal of Community Medicine, 2024)
Objectives: Describe knowledge, attitude of health staff about adverse drug reactions reporting and analyze some related factors. Research method: Cross-sectional study using semi- structure questionaire interviewing 325 health staffs of the hospital Results: Research results show that only 14,1% of health staff has knowledge about adverse drug reactions reporting, the proportion of health staff with a positive attitude towards adverse drug reactions was 73.4%. The factor related to attitudes about adverse drug reactions was the departments of health workers. Conclusion: The hospital needs to strengthen communication and training activities about regulations for adverse drug reactions reporting to health staff.
Keywords: ADR, Vinmec Times City Hospital.